What Makes Cities Healthy ? - Yusuf, Shahid, 1949- 1949- (The World Bank, 2007)
The benefits of good health to individuals and to society are strongly positive and improving the health of the poor is a key Millennium Development Goal. A typical health strategy advocated by some is increased public spending on health targeted to favor the poor and backed by foreign assistance, as well as by an international effort to perfect drugs and vaccines to ameliorate infectious diseases bedeviling the developing nations. But if the objective is better health outcomes at the least cost and a reduction in urban health inequity, the authors' research suggests that the four most potent policy interventions are: water and sanitation systems; urban land use and transport planning; effective primary care and health programs aimed at influencing diets and lifestyles; and education. The payoff from these four in terms of health outcomes dwarf the returns from new drugs and curative hospital-based medicine, although these certainly have their place in a modern urban health system. And the authors find that the resource requirements for successful health care policies are likely to depend on an acceleration of economic growth rates which increase household purchasing power and enlarge the pool of resources available to national and subnational governments to invest in health-related infrastructure and services. Thus, an acceleration of growth rates may be necessary to sustain a viable urban health strategy which is equitable and to ensure steady gains in health outcomes